2018
DOI: 10.1016/j.neo.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase-Mediated Strategy for Overcoming Non–Small Cell Lung Cancer Targeted Therapy and Chemotherapy Resistance

Abstract: Standard and targeted cancer therapies for late-stage cancer patients almost universally fail due to tumor heterogeneity/plasticity and intrinsic or acquired drug resistance. We used the telomerase substrate nucleoside precursor, 6-thio-2′-deoxyguanosine (6-thio-dG), to target telomerase-expressing non–small cell lung cancer cells resistant to EGFR-inhibitors and commonly used chemotherapy combinations. Colony formation assays, human xenografts as well as syngeneic and genetically engineered immune competent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 25 publications
(43 reference statements)
3
34
0
Order By: Relevance
“…NRTI inhibition of telomerase has been proposed to promote cellular senescence and features of premature aging in HIV patients undergoing long-term treatments 63 . In addition, several recent preclinical studies showed that 6-thio-dG is an effective treatment for melanoma, lung cancer, and glioblastoma in murine models, and increases telomere dysfunction and shortening 64 66 . Here, we uncover the mechanism by which 6-thio-dGTP compromises telomere maintenance via disrupting telomerase translocation.…”
Section: Discussionmentioning
confidence: 99%
“…NRTI inhibition of telomerase has been proposed to promote cellular senescence and features of premature aging in HIV patients undergoing long-term treatments 63 . In addition, several recent preclinical studies showed that 6-thio-dG is an effective treatment for melanoma, lung cancer, and glioblastoma in murine models, and increases telomere dysfunction and shortening 64 66 . Here, we uncover the mechanism by which 6-thio-dGTP compromises telomere maintenance via disrupting telomerase translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results with 6-thio-dG were obtained with EGFR mutant tumor cells resistant to osimertinib. In addition, Mender et al [ 9 ] demonstrated that NSCLC cells resistant to both paclitaxel and carboplatin were sensitive to 6-thio-dG. Importantly, this report showed that 6-thio-dG was orally effective leading to TIFs and tumor shrinkage in xenograft models.…”
mentioning
confidence: 84%
“…The third report examined the effects of 6-thio-dG in both targeted therapy resistant non-small cell lung cancer (NSCLC) and chemotherapy resistant NSCLC [ 9 ]. Mender and coworkers [ 9 ] showed that NSCLC cells resistant to the first-generation EGFR inhibitor, erlotinib, remained highly sensitive to 6-thio-dG even at low nanomolar concentrations. Similar results with 6-thio-dG were obtained with EGFR mutant tumor cells resistant to osimertinib.…”
mentioning
confidence: 99%
“…Even more importantly, 6‐thio‐dG appears to tackle the issues of acquired resistance and lack of efficacy for immune checkpoint blockade inhibitors and targeted therapies. Lately, 6‐thio‐dG exhibited an effective ability to overcome EGFR targeted‐ and platin‐doublet chemotherapy resistance in NSCLC, as well as in therapy‐resistant pediatric brain cancer . While targeted therapies have significantly improved the options available for unresectable or metastatic cancers, relapse almost always occurs through a variety of pathways that mediate acquired resistance.…”
Section: Telomerasementioning
confidence: 99%
“…Lately, 6-thio-dG exhibited an effective ability to overcome EGFR targeted-and platin-doublet chemotherapy resistance in NSCLC, as well as in therapy-resistant pediatric brain cancer. 44 While targeted therapies have significantly improved the options available for unresectable or metastatic cancers, relapse almost always occurs through a variety of pathways that mediate acquired resistance. Thus, it is hopeful that 6-thio-dG will work as a front line or salvage therapy towards targeting therapy-resistant cancer cells and may sensitize tumors that are refractory to checkpoint inhibitors providing long-term durable responses.…”
Section: Htert Inhibitionmentioning
confidence: 99%